The potential of traditional balinese spices against the growth of Salmonella sp in vitro - Jirna, I Nyoman; Sudarmanto, I Gede; Kurniawan, Surya Bayu; Ratih, Gusti Ayu Made; Rasyid, Burhannuddin (Jurnal Teknologi Laboratorium, 2020)
Prevention by utilizing medicinal plants can be used as an alternative treatment. This study aims to identify active antimicrobial substances and test the antimicrobial potential of traditional Balinese spices, namely Basa Selem, Basa Gede, Basa Wangen, Basa Bawang Jahe, and Basa Rajang against Salmonella sp bacteria in vitro. The True-experimental method with Posttest only-control design was used in this study, by intervening in the treatment group as well as the presence of positive and negative controls. The maceration method with 96% EtOH solvent was used to extract active substances and identify the levels of antimicrobial active substances. The TLC Spectrophotodensitometer instrument and the diffusion method (discs) were used to test antimicrobial potential. Data analysis was performed using the one-way ANOVA test. All five samples showed flavonoids, alkaloids, tannins, and phenols in qualitative tests. Based on quantitative test results of five samples, the highest compound content obtained in Basa Wangen (6.66 mg/ml of tannins), Basa Gede (3.74 mg/ml of flavonoids), Basa Bawang Jahe (2.49 mg/ml of tannins), Basa Selem (2.87 mg/ml of tannin), and Basa Rajang (6.96 mg/ml of flavonoids). There are differences in the antimicrobial potential of various types of traditional Balinese spices against the growth of Salmonella sp in vitro (sig = 0.037). The traditional Balinese spices have the antimicrobial potential of the intermediate category with a range of inhibition (16-20 mm) based on the NCCLS standard.